YouTube vlog channels in basic mathematics as e-learning during the COVID-19 pandemic - Vera Dewi Susanti; Ika Krisdiana; Wasilatul Murtafiah; Reza Kusuma Setyansah; Titin Masfingatin (PYTHAGORAS Jurnal Pendidikan Matematika, 2021)
This research aimed to produce YouTube vlog channels that are valid, practical, and effective to be used in facilitating e-learning in a basic mathematics course. The method used in this research is Research and Development (RD), which consists of four stages, namely define, design, develop, and disseminate. The subjects in this study were 62 third-semester students of the Mathematics Education Study Program at PGRI University of Madiun, Indonesia, where 50 students were field test subjects and 12 students were limited test subjects. The instruments used in this research were a validation sheet, a student response questionnaire, and a student learning outcomes test. This research produced YouTube vlog channels. Based on the validation results on teaching materials, an average score of 77% was obtained which was declared valid. Based on the student response questionnaire at the field test stage, it was obtained an average value of 75.46% which was stated to be practical. While at the limited test stage obtained a score of 81.94% which is also declared practical. Based on the learning outcomes test in the field test, the percentage of completeness was 81.82% which stated that the YouTube vlog channel was effective. Meanwhile, in the limited test stage, the completeness percentage was 82% which was also declared effective. Therefore, the produced YouTube vlog channel is feasible for use in e-learning environment.